Mistisisme Keris dan Budaya Jawa dalam Novel Wigati Karya Khilma Anis - Waningyun, Prissilia Prahesta; Afi, Mohamad (Suara Bahasa, 2023)
This study aims to describe: (1) the building blocks of the novel; (2) keris mysticism; and (3) Javanese cultural values contained in the novel Wigati by Khilma Anis. This research is a qualitative descriptive study. The approach used is a literary anthropological approach. Sources of data obtained from documents. Data collection techniques with documentation. The sampling technique used was purposive sampling technique. Data analysis was carried out by interactive data analysis. The validity of the data using theoretical triangulation. Based on the results of data analysis obtained 3 conclusions. First, the building blocks of the novel are intrinsic and extrinsic elements. Intrinsic elements include; (a) major themes about the struggle of a woman's life, minor themes, among others, the problem of kris, Javanese culture problems, love problems; (b) characters and characterizations, the main characters are Wigati (quiet, steadfast, patient odd), and Manik (kind, cheerful, caring and considerate), additional characters are Hidayat Jati (kind, intelligent, outgoing and responsible), Kang Makhrus ( kind, considerate, authoritarian), Mrs. Nyai Zulfa (kind, gentle, compassionate), Abah (firm, kind), Grandma (kind, calm, authoritative and wise), Mrs. Kinanti (kind, caring and compassionate), Ali Murtadho (kind, considerate and wise, responsibility); (c) setting: setting includes place, time, atmosphere and social setting; (d) groove: mixed; (e) point of view: mixed; (f) the message in this novel is about the dangers and effects of unregistered marriage, which means that women must have self-respect regarding unregistered marriages. Extrinsic elements include; (a) the author's biography; (b) background of creation; (c) socio-cultural conditions; (d) cultural circumstances. Both the mysticism of the keris and Javanese culture, a review of literary anthropology, is about the keris that must be brought together and the myths and customs from the time of the ancestors. Keywords: Novel, building elements, keris mysticism, Javanese cultural values